PENGATURAN HUKUM ATAS HAK BERDAULAT INDONESIA UNTUK MENGELOLA SUMBER HAYATI DI ZONA EKONOMI EKSKLUSIF INDONESIA SERTA PENEGAKANNYA - Eman Eman (Yuridika, 2017)
Pasal 1 Konvensi Montevideo tahun 1993 telah menentukan bahwa "The state as a person of international law should possess the following qualification: a.a permanent population ; b.a defined territory; c. government; and d.a capacity to enter in to relation with the other states. Article lengkap klik disini